Pendidikan Islam pada Anak Usia Dini: Peran Orang Tua dalam Membentuk Identitas Keagamaan dalam Rumah Tangga - Hafid, Abd. (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2023)
This study aimed to analyze the role of parents in shaping early childhood religious identity in the household. This research is qualitative research with a case study type. Samples in this study were taken using purposive sampling techniques in three families. Data was collected through interview, observation, and documentation techniques, and analyzed through four stages, namely data reduction, data display, verification, and conclusions. Data validity tests are carried out using the triangulation method. The results showed that in forming religious identity in early childhood, parents play more of a role as motivators by providing religious education from an early age. In addition, parents also provide concrete examples of practicing religious values in daily life in the household, and parents provide high support and motivation to children to get religious education both formally and non-formally.